Multi-stakeholder perspectives on the implementation of a clinic-based food referral program for patients with chronic conditions: a qualitative examination. Issue 9 (7th October 2022) - DePuccio, Matthew J; Garner, Jennifer A; Hefner, Jennifer L; Coovert, Nicolette; Clark, Aaron; Walker, Daniel M
Abstract: Clinic-based food referral programs (FRPs) may help alleviate food insecurity and improve access to nutritious foods by systematically identifying and referring food-insecure primary care patients to community-based food resources. The purpose of this study was to examine the barriers to and facilitators of implementation of an FRP offered to primary care patients who screen positive for food insecurity and have a qualifying chronic condition. we used a multi-stakeholder approach to conduct semi-structured interviews with healthcare providers and administrators from an academic medical center (AMC) ( n = 20), representatives of a regional foodbank and its affiliated pantries ( n = 11), and patients referred to the FRP ( n = 20), during the initial phase of FRP implementation from April to September 2020. Interviews were audio-recorded, transcribed verbatim, and coded using a deductive dominant approach that allowed for the identification of emergent themes. Seven major themes emerged across the two domains of analysis: barriers to and facilitators of FRP implementation. Key barriers were (a) provider time constraints and competing demands; (b) inadequate physician feedback regarding patient use of the program; (c) patient transportation barriers; and (d) stigma associated with food pantry use. Key facilitators of implementation included (a) program champions; (b) screening and referral coordination; and (c) addressing food pantry-related stigma. This study identifies factors that deter and facilitate the implementation of an AMC-based FRP. Our findings highlight opportunities for healthcare and community-based organizations to refine and optimize FRP models toward the ultimate aim of advancing health equity for food-insecure patients. Lay Summary: Food insecurity can make the self-management of diet-related chronic conditions (e.g., diabetes, hypertension, and obesity) difficult. Clinic-based food referral programs (FRPs) can help address the diet-related needs of food-insecure primary care patients by improving access to nutritious foods. However, the factors contributing to successful FRP implementation in primary care settings are underexplored. The focus of this study was to explore the barriers to and facilitators of implementation of an FRP offered to food-insecure primary care patients with chronic conditions seen at an academic medical center using a multi-stakeholder approach. Competing clinical and patient demands, patient transportation barriers, and food pantry-related stigma were salient factors that prevented healthcare providers and patients from engaging fully with the FRP. Inadequate provider feedback about patients' use of the FRP was also cited as a deterrent to greater provider engagement with the FRP. Critical facilitators of implementation included support and encouragement from program champions and having a coordinated referral process. The intentional branding and presentation of the FRP to eligible patients may have helped encourage its use by destigmatizing the food pantry setting. The impact of optimizing FRP implementation on patient use and program effectiveness warrants further research.